Carrot and Stick Approach: The Exploitative Leadership and Absenteeism in Education Sector - Akhtar, Muhammad Waheed; Huo, Chunhui; Syed, Fauzia; Safdar, Muhammad Arslan; Rasool, Arsalan; Husnain, Mudassir; Awais, Muhammad; Sajjad, Muhammad Shoaib (Frontiers in Psychology, 2022)
Utilizing the conservation of resources theory, this study investigates serial mediation of facades of conformity and depression between exploitative leadership and absenteeism. A total of 211 education sector employees using the convenient sampling technique took part in the survey with data collected in a time-lagged research design. Findings of the study reveal that facades of conformity and depression mediate the independent paths and play a serial mediating role between EL and absenteeism path. This study suggests that EL works as a workplace stressor, under which employees try to protect their valuable resources from further loss in the form of facades of conformity, in doing so, it leads to depression; thus, employees ultimately use absenteeism as an active coping strategy to cope with workplace stressors.